2006
DOI: 10.1152/ajpendo.00106.2005
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously imposed postprandial-like rises in systemic glucose and GLP-1 do not produce an incretin effect, suggesting an indirect mechanism of GLP-1 action

Abstract: The insulinotropic intestinal hormone GLP-1 is thought to exert one of its effects by direct action on the pancreatic beta-cell receptors. GLP-1 is rapidly degraded in plasma, such that only a small amount of the active form reaches the pancreas, making it questionable whether this amount is sufficient to produce a direct incretin effect. The aim of our study was to assess, in a dog model, the putative incretin action of GLP-1 acting directly on the beta-cell in the context of postprandial rises in GLP-1 and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 41 publications
7
35
0
Order By: Relevance
“…Our results strongly suggest that the penetration of circulating GLP-1 into the brain and consequent direct GLP-1R activation in the CNS (51), if it occurs at all, exert hardly the effect(s) on this type of the vagovagal reflex pathways and on the polysynaptic CNS activation related to the efferent limb of the vagal pathways triggered by intraportal GLP-1. In addition, the present systemic GLP-1 administration at a pharmacological dose also exhibited almost no neuronal effects on the insulin secretion, being partly in concord with the results reported previously by others (22). This concept, together with the pertinent questions, remains in the subject of further study.…”
Section: Discussionsupporting
confidence: 91%
“…Our results strongly suggest that the penetration of circulating GLP-1 into the brain and consequent direct GLP-1R activation in the CNS (51), if it occurs at all, exert hardly the effect(s) on this type of the vagovagal reflex pathways and on the polysynaptic CNS activation related to the efferent limb of the vagal pathways triggered by intraportal GLP-1. In addition, the present systemic GLP-1 administration at a pharmacological dose also exhibited almost no neuronal effects on the insulin secretion, being partly in concord with the results reported previously by others (22). This concept, together with the pertinent questions, remains in the subject of further study.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the findings in mice, intraportal GLP-1 and glucose infusions in other dog studies were found to decrease peripheral glucose levels independently of hyperinsulinemia (140). However, it should be noted that peripheral administration of GLP-1 to dogs at a similar rate is claimed not to enhance glucose-induced insulin secretion in this species (141). This is again in sharp contrast to very consistent findings in humans (135,157) and therefore suggests that dogs (and possibly mice) differ radically from humans in this respect.…”
Section: F Central Targets For Peripherallysupporting
confidence: 80%
“…As we mentioned, intraportal GLP-1 lowers systemic glucose only when paired with intraportal but not systemic glucose infusion (16,19). In addition, exendin 9 -39 (GLP-1 receptor antagonist) infused portally at a low rate attenuates the glucose-lowering effect exenatide (17). It appears that the putative GLP-1/glucose sensor might at least partially mediate the glucose-lowering effect of GLP-1 and exenatide.…”
Section: Discussionmentioning
confidence: 89%